Informal Institutions Moderate the Relationship Between Environmental Emotion and Grassland Governance Behavior. - Cai, Yu; Ni, Qi; Zhao, Minjuan (Environmental Management, 2023)
Clarifying the behavior motivation of herders participating in grassland governance has important theoretical and practical significance for the construction of ecological civilization and economic development in pastoral areas. Based on the data from 425 households in the Inner Mongolia Autonomous Region, this paper constructs a Double-Hurdle model to explore the impact of informal institutions and environmental emotion (individual emotion, collective emotion, and intergenerational dependence) on herders' grassland governance. The results show that informal institutions promote herders' willingness and payment for participating in grassland governance, and collective emotions hinder herders' participation, showing a "free-ride" mentality. Informal institutions moderate the relationship between collective emotions and grassland governance behavior. Informal institutions also help herders understand the collective sense of responsibility and morality behind grassland protection, thereby reducing the "free-ride" mentality. Therefore, it is necessary to maintain the informal institutions' role as a "glue" in the traditional culture of pastoral areas and to promote the realization of policy goals.